2021
DOI: 10.1007/s00520-021-06706-8
|View full text |Cite
|
Sign up to set email alerts
|

Oncology care providers’ awareness and practice related to physical activity promotion for breast cancer survivors and barriers and facilitators to such promotion: a nationwide cross-sectional web-based survey

Abstract: Purpose A known barrier to getting breast cancer survivors (BCSs) to engage in habitual exercise is a lack of information on recommended physical activity levels provided to them by oncology care providers (OCPs). However, the actual situation in Japan remains unclear. This study sought to clarify OCPs’ awareness and practice related to Japan’s physical activity recommendation for BCSs and to ascertain barriers to routine information provision. Methods We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, another study in 2006 suggested that there is a link between increased muscle mass through resistance training and improved quality of life in cancer survivors [20]. Nevertheless, despite all the scientific literature that we can find in favour of PA for patients with cancer, it has been seen that most oncologists recommend PA but do not prescribe the type of exercise that best fits patients with cancer based on the existing literature, among other reasons due to a lack of knowledge about how to refer to clinical PA guidelines or lack of time during medical appointments [22,23]. This study is a novel starting point and fills a gap in the literature, as no study has previously looked at this issue, bringing together the views of both groups simultaneously (i.e., oncologists and their patients).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another study in 2006 suggested that there is a link between increased muscle mass through resistance training and improved quality of life in cancer survivors [20]. Nevertheless, despite all the scientific literature that we can find in favour of PA for patients with cancer, it has been seen that most oncologists recommend PA but do not prescribe the type of exercise that best fits patients with cancer based on the existing literature, among other reasons due to a lack of knowledge about how to refer to clinical PA guidelines or lack of time during medical appointments [22,23]. This study is a novel starting point and fills a gap in the literature, as no study has previously looked at this issue, bringing together the views of both groups simultaneously (i.e., oncologists and their patients).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have carried out a series of research work to improve the level of perceived control and the QoL of patients with BC, such as psychological education intervention (22)(23)(24)(25)(26), nursing self-care educational intervention (27) and Web/or telephone intervention (28)(29)(30)(31), physical activities (11,(32)(33)(34)(35), the appearance care (36), self-disclosure intervention (37), community based intervention (38). Although these projects have achieved satisfactory results, there are few comprehensive methods including postoperative physical, psychological and social rehabilitation.…”
Section: Introductionmentioning
confidence: 99%